Lesbian Activism in the (Post-)Yugoslav Space Sisterhood and Unity - Bilić, Bojan; Radoman, Marija; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2019)
This book intertwines academic and activist voices to engage with more than three decades of lesbian activism in the Yugoslav space. The empirically rich contributions uncover a range of lesbian initiatives and the fundamental, but rarely acknowledged, role that lesbian alliances have played in articulating a feminist response to the upsurge of nationalism, widespread violence against women, and high levels of lesbophobia and homophobia in all of the post-Yugoslav states. By offering a distinctly intergenerational and transnational perspective, this collection does not only shed new light on a severely marginalised group of people, but constitutes a pioneering effort in accounting for the intricacies - solidarities, joys, and tensions - of lesbian activist organising in a post-conflict and post-socialist environment. With a plethora of authorial standpoints and innovative methodological approaches, the volume challenges the systematic absence of (post-)Yugoslav lesbian activist enterprises from recent social science scholarship. Lesbian Activism in the (Post-)Yugoslav Space will be of interest to students and scholars across a range of disciplines, including gender studies, history, politics, anthropology, and sociology. .
1. Introduction Recovering/Rethinking (Post-)Yugoslav Lesbian Activisms; Bojan Bilić -- 2. Yearning for Space, Pleasure, and Knowledge: Autonomous Lesbian and Queer Feminist Organising in Ljubljana; Teja Oblak and Maja Pan -- 3. Cartographies of Fear and Freedom: Lesbian Activists in the First Belgrade and Zagreb Pride Parades: Sanja Kajinić -- 4. Sisterhood beyond Borders: Transnational Aspects of (Post-)Yugoslav Lesbian Activism; Irene Dioli -- 5. Breaking the Silence: Lesbian activism in Macedonia; Irena Cvetkovic -- 6. Searching for a Lesbian Voice: Women's Non-Heterosexual Activism in Montenegro; Marina Vuković and Paula Petričević -- 7. (In)visible Presences: PitchWise Festival as a Space of Lesbian Belonging in Bosnia and Herzegovina; Adelita Selmić and Bojan Bilić -- 8. Conclusion: Discovering the Lesbian in Us: On Our Ongoing, Never-Ending Struggles; Marija Radoman. .
Keywords: Ethnology; Social structure; Equality; Identity politics; Sociocultural Anthropology; Social Structure; Politics and Gender